Menyusui Eksklusif, Penyakit Diare Dengan Kejadian Stunting Pada Anak Balita Usia 24-59 Bulan Di Wilayah Kerja Puskesmas Sangkub - Rivolta G.M. Walalangi; Olfie Sahelangi; Rudolf B. Purba; Nilam Sentika (Jurnal GIZIDO, 2019)
Stunting is a chronic condition of a child's poor linear growth which is an accumulation of the effects of various factors such as poor nutrition and health before and after the birth of the child. Riskesdas data in 2013 amounted to 37.2% of Indonesian children experiencing stunting. This figure increased compared to 2010 (35.6%) and 2007 (36.8%). This study was conducted to analyze exclusive breastfeeding status and diarrheal disease as risk factors for stunting in children under the age of 24-59 months in the working area of ​​Sangkub Community Health Center, Sangkub Subdistrict, Bolaang Mongondow Utara Regency. This type of research is Analytical Observational with a Retrospective Cohort design. Conducted in January - February 2019 in the working area of ​​the Sangkub Community Health Center, Sangkub District, North Bolaang Mongondow Regency. with a sample size of 40 toddlers. The sampling technique is consecutive sampling.The results showed that the results of statistical tests using the Fisher's Exact Test test obtained a significant level (p = 0.037) which means p = <0.05. From these results it can be seen that there is a significant relationship between exclusive breastfeeding status and the incidence of stunting in infants aged 24-59 months in the working area of ​​Sangkub Community Health Center, Sangkub Subdistrict, North Bolaang Mongondow Regency and obtained a significant level (p = 1,000) means p => 0.05, which means that there is no significant relationship between diarrheal disease and the incidence of stunting in infants aged 24-59 months in the working area of ​​Sangkub Community Health Center, Sangkub District, North Bolaang Mongondow Regency.